Time-resolved IR spectroscopy of a trinuclear palladium complex in solution1. Issue 21 (7th June 2015) - Zimmer, M.; Rupp, F.; Singer, P.; Walz, F.; Breher, F.; Klopper, W.; Diller, R.; Gerhards, M.
<x xml:space="preserve">Abstract</x> Time-resolved IR spectroscopic methods covering the femto- to microsecond range in combination with (TD-)DFT computations were used to investigate the electronically excited state structure of a trinuclear Pd complex.